High sensitivity Thomson spectrometry: analysis of measurements in high power picosecond laser experiments. (1st January 2022) - Scisciò, M.; Consoli, F.; Salvadori, M.; Rosmej, O. N.; Zähter, S.; Di Giorgio, G.; Andreoli, P.L.; Cipriani, M.; Cristofari, G.; De Angelis, R.; Günther, M. M.; Gyrdymov, M.; et al.
Abstract: Thomson spectrometers (TS) are designed to detect and distinguish protons from heavier ions in experiments of intense laser-matter interaction. The combination of electric and magnetic field allows for deflecting ion species with different mass-to-charge ratio on different trajectories. However, even small distortions of the internal fields of the device can lead to a degradation of the measurement quality. Hence, TS are sensitive to both high electromagnetic pulses (EMPs) and fields due to static charge accumulation caused by the interaction. Here we report on the analysis of data obtained with a TS designed to have high sensitivity and robustness with, optimized shielding against EMPs, even when the device is placed at short distances from the interaction point, where the electromagnetic radiation is more intense. To test this, the spectrometer was thus placed ∼50 cm far from the target during an experiment at the PHELIX laser at GSI (∼180 J energy, >10 20 W/cm 2 intensity, sub-picosecond laser pulses on solid targets). Despite the presence of strong EMPs (beyond 100 kV/m at 1 m distance from the target), the tests were successful and the TS was able to retrieve a good-quality signal. Indeed, the close proximity to the interaction point caused a significant number of electrons, produced by the intense laser-target interaction, entering the TS and causing internal electrostatic fields up to tens of kV/m. These induced fields altered the trajectories of the detected ions, making the interpretation and characterization of the particle species not straightforward. This effect was analyzed with ad-hoc particle tracking simulations. This study is of high importance for the effective implementation of this type of high-sensitivity TSs in experiments with PW-power lasers.